AN APPROACH TO THE DROWNED SOULS, A COLLECTION OF POEMS BY VLADISLAV PETKOVIC DIS - Бранка М. Јакшић-Провчи (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2010)
Dis's modernistic poetry has attracted considerable attention of the literary critics in this century with the vast portion of the critical thought directed mainly towards his collection of poems The Drowned Souls. Since Dis has been present in the high school curricula for decades, this paper suggests a possible model for the interpretation of the primarily prologue poem The Dungeon and its correspondence with the other poems of the collection. The main principle is the approach to the collection as a homogeneous whole. The taught interpretation of the central themes of the poem will pave the way for the students' independent approach to individual poems in the collection.